VAR consultation patterns and their association with fouls and misconduct: an analysis of the top five European football leagues - Nazarudin, M. N.; Abdul Majeed, A. P. P.; Musa, R. M.; Raj, N. B.; Kuan, G.; Abu Osman, N. A. (PLOS ONE, 2025)
Delays and controversies surrounding Video Assistant Referee (VAR) consultations have raised concerns in European football, particularly regarding the types of infractions that prompt referee interventions. This study analysed referee data from 6,232 matches across five seasons in the top five European leagues to identify the foul and misconduct behaviours most strongly associated with VAR referrals. Using clustering and logistic regression, we found that a limited set of offences, most notably handball, off-the-ball challenges, professional fouls, and simulation, were consistently linked to higher consultation frequency. While descriptive comparisons suggested some variation between leagues, league affiliation itself was not a significant predictor once foul type was considered. The findings indicate that VAR is predominantly engaged for offences that are both subjective and potentially decisive in match outcomes. These insights have practical implications for referees, coaches, and players by highlighting the need for strategies that minimise unnecessary consultations, improve game flow, and enhance the consistency of officiating in elite football.